2016
DOI: 10.1021/jacs.5b13496
|View full text |Cite
|
Sign up to set email alerts
|

Fullerene-Assisted Photoinduced Charge Transfer of Single-Walled Carbon Nanotubes through a Flavin Helix

Abstract: One of the greatest challenges with single-walled carbon nanotube (SWNT) photovoltaics and nanostructured devices is maintaining the nanotubes in their pristine state (i.e., devoid of aggregation and inhomogeneous doping) so that their unique spectroscopic and transport characteristics are preserved. To this effect, we report on the synthesis and self-assembly of a C60-functionalized flavin (FC60), composed of PCBM and isoalloxazine moieties attached on either ends of a linear, C-12 aliphatic spacer. Small amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…Similarly, Varadwaj et al showed that charge transfer is a factor controlling the equilibrium constants of late first-row transition metal complexes (the so-called Irving-Williams series) [96], and have suggested it to be a major driving force to provide geometrical stability to organic-inorganic perovskites in gas-phase adducts [97][98][99]. Given the conflicting views on charge transfer emerging from various groups, and given that the concepts of charge transfer, charge separation, as well as charge recombination, have been widely utilized to develop a variety of donor-acceptor functional materials (e.g., organic photovoltaics) [71,[100][101][102][103][104], it seems to us from the various conflicting arguments summarized above that the concept of charge transfer is yet to be fully understood. There is clearly a pressing need for rigorous methodical developments to resolve the issue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Varadwaj et al showed that charge transfer is a factor controlling the equilibrium constants of late first-row transition metal complexes (the so-called Irving-Williams series) [96], and have suggested it to be a major driving force to provide geometrical stability to organic-inorganic perovskites in gas-phase adducts [97][98][99]. Given the conflicting views on charge transfer emerging from various groups, and given that the concepts of charge transfer, charge separation, as well as charge recombination, have been widely utilized to develop a variety of donor-acceptor functional materials (e.g., organic photovoltaics) [71,[100][101][102][103][104], it seems to us from the various conflicting arguments summarized above that the concept of charge transfer is yet to be fully understood. There is clearly a pressing need for rigorous methodical developments to resolve the issue.…”
Section: Introductionmentioning
confidence: 99%
“…(a) Unit cell and 2 × 2 supercell and (b) [002] slicing pattern. (c)[101] Slicing pattern. Type-II and -I bonding patterns between interacting monomers in the crystal are shown in (d,e), respectively, with the IGM isosurfaces corresponding to these interactions in green volumes.…”
mentioning
confidence: 99%
“…1618 On the other hand, noncovalent chemistry occurs under equilibrium, and offers the possibility of switching the interactions on and off in response to stimuli. 1921 …”
Section: Introductionmentioning
confidence: 99%
“…Flavin is a naturally occurring electron mediator, and has been used in several articial molecular assembling systems, for example, by incorporating it into self-assembled monolayers [19][20][21] and combination with single-walled carbon nanotubes. 22 In the present paper, avin is therefore introduced into peptide nanotubes to study the way how the 3-dimensional arrangement of the avin groups in the peptide nanotube bundles inuences the electric outputs of the molecular assemblies on a gold substrate. Two kinds of cyclic tri-b-peptides of cyclo(b-Asp(avin)-b-Ala-b-Ala) (C3FAA) and cyclo(b-Asp(avin)-ethylenediamine-succinic acid) (C3FES) are designed ( Fig.…”
Section: Introductionmentioning
confidence: 99%